Rancang Bangun Aplikasi Sistem Informasi Manajemen Inventaris Barang Berbasis Desktop pada CV Kylaboquette - Muhammad Zaky; Alil Mu’afi; Diaz Nuraji; Muhammad Rio Ferdianto; Mohammad Abie Syah Harianto (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This study aims to develop a desktop-based inventory management information system application for CV Kylaboquette. The purpose of this application is to streamline the process of inventory recording, monitoring, and reporting, which has traditionally been done manually. By adopting the Waterfall methodology, the development process includes requirement analysis, system design, coding, program testing, and implementation. The resulting application is expected to enhance operational efficiency, reduce human error risks, and improve service quality. Through this system, CV Kylaboquette can manage inventory in real-time, ensuring accurate and up-to-date information availability.